Pengaruh Metode Indexcard, Motivasi Belajar dan Penggunaan Media Film Terhadap Hasil Belajar Sejarah - Diyah Yudha Trisanti; Soedjijono; Endah Andayani (Jurnal Penelitian dan Pendidikan IPS, 2021)
To analyze the effect of using the index card match method with historical learning outcomes in class X SMKN 10 Malang. The method used ex-post-facto, because researchers relate to variables that have occurred and they do not need to give treatment to the variables examined by the results of research, namely the variables that have the greatest standardization coefficient on historical learning outcomes is the index card match of 0.524. Thus the index card match is the most influential variable or has the most dominant influence on learning outcomes in history.